SPECIALITI LANGUAGE IN THE COMMUNICATIVE ASPECT - Yuldasheva Yulduz Uzgenovna (Bright Mind Publishing, 2025)
Communicative method is occurrence in demand in up-to-date terms of education, where educational process is the model of communication. Specialty language is regarded in communicative aspect on the texts of sublanguage in this article. Individual approach for the development of communicative skills is offered.
Keywords: Specialty language, communicativeness, in demand, motivation, problem, individualization, integration, differentiation, text resources.